PERSEPSI PETANI TERHADAP PROGRAM DEMONSTRASI AREA BUDIDAYA TANAMAN SEHAT PADI (STUDI KASUS DI KECAMATAN POLOKARTO KABUPATEN SUKOHARJO) - Luthfi Agung Ardhianta; Retno Setyowati; Agung Wibowo (AGRITEXTS: Journal of Agricultural Extension, 2020)
The objectives of the study were to assess, the perception of farmers on the program for demonstration area of healthy rice cultivation, examine the characteristics of the factors forming the perception of farmers participating in the program for demonstration area of healthy rice cultivation, analyze of the correlation between the factors forming perceptions farmers to demonstration healthy rice cultivation area program. The study used the method of descriptive by using survey techniques. The location was in Polokarto, Sukoharjo, taking 2 villages implementing the program. The population was the member farmers of the Pilangrejo farmer group and the Kenteng Farmer Group. The study used a proportional random sampling technique and respondents were taken as many as 60 farmers. The data in this study were presented with a Likert scale and to test the correlation used Spearman rank analysis and t-test. The results showed that, the factors forming perceptions were age, formal education, non-formal education, land area, income, experience, and motivation,  Farmers’ perceptions of the understanding, goals, benefits, and activities contained in the program demonstration area of healthy rice crop cultivation were good, There was a significant correlation between income and experience of farmers to the program demonstration area of healthy rice cultivation. Whereas age, formal education, non-formal education, land area, and motivation were not significantly related to farmers’ perceptions of the program for the cultivation of healthy rice.